Death rights: romantic suicide, race, and the bounds of liberalism - Koretsky, Deanna P. (SUNY Press Open Access Ser., 2021)
Intro -- Contents -- Acknowledgments -- Introduction -- The Argument -- Contexts -- Methods -- Chapters -- Chapter 1 Liberty and Death -- John Locke, Property, and Self-Destruction -- The Dying Negro and the Politics of Freedom -- The Suicide Note and the Poetics of Personhood -- Life After (Social) Death -- Chapter 2 Chained to Life and Misery -- Foundations: Mary Wollstonecraft, Suicide, and the Critique of Sensibility -- Racial Sensibility and the Bounds of "Woman" in Mary Robinson and Claire de Duras -- Flickering Whiteness in Felicia Hemans's Suicide Poems -- Revising Racial Sensibility in The Story of Mattie J. Jackson -- Chapter 3 Writ in Water -- (Im)possible Life: Blackness and Romanticism -- Equiano's Black Ecology -- Black Optimism and Equiano's Poetic Turn -- Keats's Posthumous Life -- Chapter 4 In Sympathy -- Frankenstein and the Suicide Debates -- The Social Function of Sympathy -- Friendly Antipathies -- Blackness and the End(s) of Liberalism -- Chapter 5 Marvelous Boys -- The Mythic Structure of Romantic Suicide -- Conclusion: Black Lives and Dead White Guys -- Notes -- Bibliography -- Index.